Was vom Himmel kommt Stoffanalytische Zugänge zu antiken Mythen aus Mesopotamien, Ägypten, Griechenland und Rom - Gabriel, Gösta Ingvar; Kärger, Brit; Zgoll, Annette; Zgoll, Christian (Mythological Studies, 2021)
In ancient myths, the sky is a numinous space. What comes from it is of outstanding importance. This transdisciplinary volume by the Collegium Mythologicum explores myths that involve transfers from the sky. The volume utilizes the hylistics established by Christian Zgoll to combine and compare its findings. Ultimately, transfers from the sky prove to be indicators of numinosity in mythical garb.